Lemmus trimucronatus distribution points - Knowles, L. Lacey; Massatti, Rob; He, Qixin; Olson, Link E.; Lanier, Hayley C. (Dryad Digital Repository, 2017)
Distribution points used to generate ENMs for Lemmus trimucronatus